2011
DOI: 10.3126/jnps.v31i2.3634
|View full text |Cite
|
Sign up to set email alerts
|

A Scenario of Poisoning in Children in Manipal Teaching Hospital

Abstract: Objective: To see the pattern and prevalence of poisoning in children in Manipal Teaching Hospital, Pokhara. The cases were also considered in relevance to the age groups with various agents, the commonly observed clinical features in various poisonings and mortality. Study design: Hospital based retrospective study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The previous study from this institute and Patan showed 30% and 33% mortality respectively. 6,7 However, mortality is high as compared to other poisoning. Higher mortality in mushroom poisoning was most likely due to severe liver toxicity and late manifestation of symptoms leading to late arrival to emergency.…”
Section: Discussionmentioning
confidence: 99%
“…The previous study from this institute and Patan showed 30% and 33% mortality respectively. 6,7 However, mortality is high as compared to other poisoning. Higher mortality in mushroom poisoning was most likely due to severe liver toxicity and late manifestation of symptoms leading to late arrival to emergency.…”
Section: Discussionmentioning
confidence: 99%
“…A cute poisoning is an important cause of emergency department visits and hospital admission in children 1 and it is one of the poten ally preventable causes of childhood morbidity and mortality in Nepal 1,2 . The eff ects of poisoning have both short and long term health implica ons in children as well as in parents.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] Boys had a higher incidence of poisoning at 64.8% compared to girls, which is consistent with findings from other Asian studies. [16][17][18][19] The male-to-female ratio was twofold up to the age of 10 years, after which the ratio equalized beyond this age threshold.…”
Section: Discussionmentioning
confidence: 99%